An additional dose of viral vector COVID-19 vaccine and mRNA COVID-19 vaccine in kidney transplant recipients: A randomized controlled trial (CVIM 4 study) - Bruminhent J. (2023)
Immunogenicity following an additional dose of Coronavirus disease 2019 (COVID-19) vaccine was investigated in an extended primary series among kidney transplant (KT) recipients. Eighty-five KT participants were randomized to receive either an mRNA (M group; n = 43) or viral vector (V group; n = 42) vaccine. Among them, 62% were male, with a median (IQR) age of 50 (43–59) years and post-transplantation duration of 46 (26–82) months. At 2 weeks post-additional dose, there was no difference in the seroconversion rate between the M and V groups (70% vs. 65%, p =.63). A median (IQR) of anti-RBD antibody level was not statistically different between the M group compared with the V group (51.8 [5.1–591] vs. 28.5 [2.9–119.3] BAU/ml, p =.18). Furthermore, the percentage of participants with positive SARS-CoV-2 surrogate virus neutralization test results was not statistically different between groups (20% vs. 15%, p =.40). S1-specific T cell and RBD-specific B cell responses were also comparable between the M and V groups (230 [41–420] vs. 268 [118–510], p =.65 and 2 [0–10] vs. 2 [0–13] spot-forming units/106 peripheral blood mononuclear cells, p =.60). In conclusion, compared with an additional dose of viral vector COVID-19 vaccine, a dose of mRNA COVID-19 vaccine did not elicit significantly different responses in KT recipients, regarding either humoral or cell-mediated immunity. (TCTR20211102003).